Implementation of the Ismubaris Curriculum (Islamic Studies, Muhammadiyah Ideology, Arabic, and English) - Sormin, Darliana; Siregar, Ihsan; Rambe, Nursaima; Siregar, Rosmaimuna; Lubis, Jumaita Nopriani; Kholijah, Adek (Institut Agama Islam Daruttaqwa Gresik, 2025)
This research is motivated by the importance of strengthening students' Islamic and national character through an integrated curriculum, particularly within Muhammadiyah schools. The ISMUBARIS curriculum (Al-Islam, Kemuhammadiyahan, Arabic, and English) is an educational innovation designed to shape students who are academically excellent, religiously grounded, and proficient in foreign languages. The primary objective of this study is to investigate the implementation of the ISMUBARIS curriculum at Muhammadiyah 1 Private Elementary School in Padangsidimpuan, which began implementing the curriculum in 2023. This research employs a qualitative approach using a case study method. Data were collected through observations, in-depth interviews with school principals, teachers, and students, as well as documentation of curriculum and teaching materials. The data analysis technique comprises four stages: data collection, data reduction, data presentation, and concluding. The findings reveal that the ISMUBARIS curriculum has been implemented across all grade levels, although the depth of material varies according to students’ developmental stages. The curriculum is not only taught as standalone subjects but also serves as a core spirit integrated into all areas of learning. Challenges include the absence of specialized teacher training and a lack of formal socialization from the educational board. Overall, student achievement is positive across cognitive, affective, and psychomotor domains. The implications of this research emphasize the need for strong synergy among schools, families, and communities to reinforce students’ Islamic character, as well as the importance of supportive policies to sustain and optimize the implementation of the ISMUBARIS curriculum in Muhammadiyah schools.